Detection of Salmonella typhimurium ATCC 14028 in Powder Prepared Traditional Medicines Using Real-Time PCR - Alfi Sophian; Ratna Purwaningsih; Muindar Muindar; Eka Putri Juniarti Igirisa; Muhammad Luthfi Amirullah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
The detection of Salmonella typhimurium ATCC 14028 using real-time PCR on powdered traditional medicinal products was carried out in the microbiology and molecular biology testing laboratory of the Food and Drug Administration in Gorontalo. This research aims to provide a reference for alternative testing methods in testing the products of traditional powder preparations on the market. The sample consisted of 10 traditional powder preparations spiked with positive control of S. typhimurium ATCC 14028 phase 2. The method used in the study was real-time PCR analysis using the SYBR® Green method, while DNA isolation using the direct PCR method. Data analysis was performed by analyzing the sample's melting temperature (Tm) curve and comparing it with positive control. The results showed that S. typhimurium ATCC 14028 was detected in samples at an average Tm value of 84.18°C, with ranges of 84.0-84.5°C. For positive control, the Tm value was at 85.2°C, while for the negative control, the Tm value was not detected. Based on these data, it can be concluded that S. typhimurium ATCC 14028 in traditional medicine products powder preparations can be detected using real-time PCR.